Kualitas Hasil Uji Limbah Pool-Plasma Komponen Packed Red-Blood Cell (PRC) Sebagai Antisera Golongan Darah ABO - Wahdaniah, Wahdaniah; Margini, Fitria; Sabolakna, Asep (Jurnal Laboratorium Khatulistiwa, 2022)
PRC is the most needed component for current blood transfusion. Plasma is one of the separation product of PRC from whole blood. These components are often discarded due to low plasma transfusion requirements. The residual plasma contains natural ABO agglutinins that can be utilized as polyclonal antisera in blood grouping tests. This study aims to determine the quality of pool residual plasma of PRC component as the ABO blood grouping antisera. This research uses descriptive analytic design in the form of comparative study. Samples of the test materials and the testers were obtained by purposive sampling, which consisting of each 20 units of A, B and O (positive control) plasma, and also 2 units of AB plasma (negative control) as the test materials, and each 25 of A and B fresh blood specimens as the tester materials. All of those materials should meet the inclusion and exclusion criteria of this study. According to their blood type, each of the plasma were mixed proportionaly according to its weight. Then, each pool-plasma and the commercial antisera were tested together against the same fresh blood specimens by the slide method. The degree of each agglutination was observed by 2 panelists, and then analyzed statistically by Wilcoxon Signed Rank Test with error rate (Î±) = 5%. The degree of agglutination by using the B pool-plasma against the A fresh blood was obtained in proportions of 8.0% (2+), 38.0% (3+) and 54.0% (4+) with the difference in proportion of 34.0% (3+) higher and 42.0% (4+) lower than anti-A commercial antisera. Meanwhile, by using the A pool-plasma against the B fresh blood was obtained in proportion of 18,0% (3+) and 82,0% (4+) with difference in proportion of 18,0% (3+) higher and 18,0% (4+) lower than anti-B commercial antisera. There are significant differences between the commercial antisera and the pool residual plasma as blood grouping test materials based on observation of all panelists (p value = 0.000).